Quelques exemples de modelisation et simulation du delaminage en 3D - Gornet, Laurent; Hochard, Christian; Ladeveze, Pierre (European Journal of Computational Mechanics, 1998)
The optimisation of laminate composite structures requires the computation of complete fracture phenomena. The aim of this paper is to present, within the framework of the finite element method, a damage computational approach which allows a true simulation of laminate delamination. The meso-model used is based on damage mechanics and the numerical implementation is presented. Simulation of classical delamination tests and complex 3D examples show the efficiency of the proposed approach.